Innate immune memory after brain injury drives inflammatory cardiac dysfunction - Simats, Alba; Zhang, Sijia; Messerer, Denise; Chong, Faye; Beşkardeş, Sude; Chivukula, Aparna Sharma; Cao, Jiayu; Besson-Girard, Simon; Montellano, Felipe A.; Morbach, Caroline; Carofiglio, Olga; Ricci, Alessio; et al. (Cell, 2024)
The medical burden of stroke extends beyond the brain injury itself and is largely determined by chronic comorbidities that develop secondarily. We hypothesized that these comorbidities might share a common immunological cause, yet chronic effects post-stroke on systemic immunity are underexplored. Here, we identify myeloid innate immune memory as a cause of remote organ dysfunction after stroke. Single-cell sequencing revealed persistent pro-inflammatory changes in monocytes/macrophages in multiple organs up to 3 months after brain injury, notably in the heart, leading to cardiac fibrosis and dysfunction in both mice and stroke patients. IL-1β was identified as a key driver of epigenetic changes in innate immune memory. These changes could be transplanted to naive mice, inducing cardiac dysfunction. By neutralizing post-stroke IL-1β or blocking pro-inflammatory monocyte trafficking with a CCR2/5 inhibitor, we prevented post-stroke cardiac dysfunction. Such immune-targeted therapies could potentially prevent various IL-1β-mediated comorbidities, offering a framework for secondary prevention immunotherapy.
Gesehen am 07.11.2024